STUDI BIODEGRADASI FILM BIOPLASTIK TEMBAKAU MENGGUNAKAN BAKTERI EM4 - M. Muhaimin; Triana Lindriati; Andrew Setiawan Rusdianto (UPT Penerbitan Universitas Jember, 2018)
Plastic waste into one of global-scale environmental problems. Types of plastic in circulation in the community is a synthetic plastic from raw petroleum are limited in number, could not be renewed, and the synthetic plastic raw material petroleum difficult degraded by microorganisms or difficult overhauled in biodiversity (nonbiodegradable) thus leading to a buildup of plastic waste which have an impact on environmental pollution so that required the development of plastic that is environmentally friendly and sustainable, known as bioplastic (biodegradable plastic). The research method used was experimental research methods using different treatment. Treatment 1 uses only the base of cassava starch as control (P0), treatment of cassava starch base material 2 added powder tobacco stem 1 gram (P1), treatment of cassava starch 3 basic ingredients added to tobacco stems 2 grams of powder (P2). This research aims to test the ability of biodegradable film bioplastic produced with the help of bacteria EM4. From the test results obtained that the film made from bioplastic starch cassava powder tobacco stem with the addition of biologically degraded on the 6th day.